2015
DOI: 10.1128/iai.00345-15
|View full text |Cite
|
Sign up to set email alerts
|

Host-Like Carbohydrates Promote Bloodstream Survival of Vibrio vulnificusIn Vivo

Abstract: Sialic acids are found on all vertebrate cell surfaces and are part of a larger class of molecules known as nonulosonic acids. Many bacterial pathogens synthesize related nine-carbon backbone sugars; however, the role(s) of these non-sialic acid molecules in host-pathogen interactions is poorly understood. Vibrio vulnificus is the leading cause of seafood-related death in the United States due to its ability to quickly access the host bloodstream, which it can accomplish through gastrointestinal or wound infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 54 publications
(65 reference statements)
0
34
1
Order By: Relevance
“…The same is true among several other taxa that are known to produce sialic acids or related molecules Lubin et al 2015).…”
Section: Discussionmentioning
confidence: 50%
“…The same is true among several other taxa that are known to produce sialic acids or related molecules Lubin et al 2015).…”
Section: Discussionmentioning
confidence: 50%
“…vulnificus also variably produces sialic acid-like molecules presented as modifications to the lipopolysaccharide, which likely evolved to facilitate a marine environmental lifestyle. However, these modifications show significant benefit to survival during bloodstream infections and dissemination in vivo [15]. In addition, sialic acid is linked to metabolic fitness in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…On the same theme, sialic acid-like carbohydrates factor into the pathogenicity of V . vulnificus , since these host-like molecules are required for full motility and biofilm formation, providing a benefit for bacterial survival in the bloodstream [15]. …”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of septicaemia, competition experiments revealed that the V. vulnificus sialic acid synthase mutant strain has a 300-fold lower chance of survival compared with the wild-type strain. Sialic acid plays a critical role in biofilm formation and motility, and also protects V. vulnificus from the host immune response (Lubin et al, 2015). These data imply a critical role of the enzymes responsible for sialic acid utilization in the survival of V. vulnificus.…”
Section: Introductionmentioning
confidence: 76%